CREATING NEW INCOME OPPORTUNITIES FOR THE POPULATION BY IMPROVING THE BUSINESS ENVIRONMENT (Marketing Journal, 2025)
This article provides a scientific overview of modern approaches to improving the entrepreneurial environment, increasing household incomes, reducing poverty, and the outcomes of ongoing reforms in Uzbekistan. It explores research focused on entrepreneursh ip development and poverty reduction, highlights new opportunities to boost income levels, identifies key poverty -reducing factors, and examines legal aspects that support the growth of private business.
Keywords: small business; digital technologies; private entrepreneurship; poverty reduction; innovation; socio -economic opportunities; income growth